Combined constraint for single image dehazing. Issue 22 (8th October 2015) - He, Renjie; Wang, Zhiyong; Fan, Yangyu; Feng, David Dagan
Abstract : Existing single image dehazing techniques have limitations on estimating accurate transmission maps for pixels which do not meet the assumption of the dark channel prior. A combined constraint is presented for single image dehazing by taking both geometric and natural characteristics of outdoor images into consideration. The combined constraint can be applied to various regularisation‐based optimisation frameworks. Both qualitative and quantitative comparisons with the state‐of‐the‐art dehazing approaches indicate the superiority of the proposed constraint.